Chapter Q&A with Annamaria Pagliaro: From Italy to Australia and Back - Pagliaro, Annamaria (Biblioteca di Studi di Filologia Moderna, 2022)
This essay-interview traces Annamaria Pagliaro's contribution to cultural relationships, cultural and educational exchanges between Australia and Italy, particularly based on her work as Director of the Monash University Prato Centre (2005-2008).